Early silent coronary bypass graft occlusion following coronary bypass surgery, implication of routine coronary computed tomography angiography - Salikhanov, Islam; Koechlin, Luca; Gahl, Brigitta; Reuthebuch, Oliver; Zellweger, Michael; Haaf, Philip; Bremerich, Jens; Pradella, Maurice; Müller, Christian; Berdajs, Denis (Frontiers in Cardiovascular Medicine, 2024)
Objective: To evaluate incidence and predictors of early silent bypass occlusion following coronary bypass surgery using cardiac computed tomography angiography.Methods: A total of 439 consecutive patients with mean age of 66 ± 10 years comprising 17% (n=75) females underwent isolated coronary bypass surgery followed by CT scan before discharge.Graft patency was evaluated in 1319 anastomoses where 44% (n=580) arterial and 56% (n=739) vein graft anastomosis were performed. Cardiovascular risk factors, demographics, and intraoperative variables were analyzed. We conducted univariable and multivariable logistic regression analyses to analyze variables potentially associated with graft occlusion following CABG. Variables included gender, surgery duration, graft flow, pulsatility index, vein vs. artery graft, and recent MI.Results: Overall incidence of graft occlusion was 2.4% (31/1319), and it was diagnosed in 6.6% (29/439) of patients. The difference in occlusion between arterial (2.1%) and vein (2.6%) grafts was not significant, p=0.68. The duration of intervention p=0.034, cross clamp time p=0.024 as well the number of distal anastomosis p=0.034 were significantly higher in occlusion group. The univariate and multivariate logistic regression indicated duration of surgery being predictive for bypass graft occlusion with OR=1.18; 95% CI: 1.01 to 1.38; p=0.035.Early graft occlusion was associated with surgical factors. The number of distant anastamoses, along duration of surgical intervention were, significantly influenced the risk of EGO. Prolonged procedural time reflecting complex coronary pathology and time-consuming revascularization procedure was as well associated to the elevated risk of occlusion.